Zlatouhi ponirek Podiceps auritus - Kmecl, Primož (Acrocephalus, 1991)
At Sečovlje on 30th December 1990 (incl. 88 Great Crested Grebes, 35 Black-throated Divers, 11 Red-breasted Mergansers, 400 Wigeons, a female Hen Harrier and wintering White Stork). Another Slavonian Grebe at Lake Cerkica on13th January 1991
Keywords: Birds; Cerkniško jezero; Ornithology; ornitologija; Podiceps auritus; ptiči; Slovenia; Slovenija; zlatouhi ponirek